2019
DOI: 10.1080/22221751.2018.1564630
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with whole cell but not acellular pertussis vaccines primes CD4 T RM cells that sustain protective immunity against nasal colonization with Bordetella pertussis

Abstract: Protective immunity wanes rapidly after immunization of children with acellular pertussis (aP) vaccines and these vaccines do not prevent nasal colonization or transmission of Bordetella pertussis in baboons. In this study, we examined the role of tissue-resident memory T (T RM ) cells in persistent protective immunity induced by infection or immunization with aP and whole-cell pertussis (wP) vaccines in mice. Immunization of mice with a wP vaccine protected agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 46 publications
5
130
0
2
Order By: Relevance
“…A protective role for CD4 + T RM at mucosal surfaces has recently been described for a number of bacterial pathogens of public health significance. 1,2,[28][29][30][31][32][33][34] Exposure to live pneumococcus in the nasopharynx protects mice against subsequent homologous or heterologous pneumococcal challenge. 21,22 Hence, we hypothesized that I.N.…”
Section: Resultsmentioning
confidence: 99%
“…A protective role for CD4 + T RM at mucosal surfaces has recently been described for a number of bacterial pathogens of public health significance. 1,2,[28][29][30][31][32][33][34] Exposure to live pneumococcus in the nasopharynx protects mice against subsequent homologous or heterologous pneumococcal challenge. 21,22 Hence, we hypothesized that I.N.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, earlier waning of protective immunity and the circulation of B. pertussis variants depleted of vaccine-included antigens further favor the increase in pertussis disease [74]. Studies in immunized children have reported that antibody responses and protective immunity wane 3-5 years after immunization with acellular pertussis (aP) vaccines, which may reflect poor induction of memory T and/or B cells [76][77][78].…”
Section: Pertussis Vaccinationmentioning
confidence: 99%
“…Yet another cause for the increase is the differences detected in the immune response triggered by the whole cell vaccine (Th17) vs. the acellular vaccine (Th2) (51,(55)(56)(57). It is important to highlight that while neither whole-cell nor acellular vaccines confer long-lasting immunity, and the merits of both responses have been debated in recent years, the general consensus agrees on advantages to skewing T cell response toward Th1/Th17 immunity (58)(59)(60)(61).…”
Section: The Bordetellae; Biology; and Experimental Systemmentioning
confidence: 99%